Economic Impacts from the Promotion of Renewable Energy Technologies - The German Experience - Manuel Frondel; Nolan Ritter; Christoph M. Schmidt; Colin Vance (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
The allure of an environmentally benign, abundant, and cost-effective energy source has led an increasing number of industrialized countries to back public financing of renewable energies. Germany's experience with renewable energy promotion is often cited as a model to be replicated elsewhere, being based on a combination of far-reaching energy and environmental laws that stretch back nearly two decades. This paper critically reviews the current centerpiece of this effort, the Renewable Energy Sources Act (EEG), focusing on its costs and the associated implications for job creation and climate protection. We argue that German renewable energy policy, and in particular the adopted feed-in tariff scheme, has failed to harness the market incentives needed to ensure a viable and cost-effective introduction of renewable energies into the country's energy portfolio. To the contrary, the government's support mechanisms have in many respects subverted these incentives, resulting in massive expenditures that show little long-term promise for stimulating the economy, protecting the environment, or increasing energy security.
Keywords: Q28; Q42; Q48; 330; Energy policy; energy security; climate; employment; Förderung regenerativer Energien; Stromtarif; Administrierter Preis; Wirkungsanalyse; Kritik; Elektrizität; Konsumentenverhalten; Klimaschutz; Deutschland